2022
DOI: 10.3889/oamjms.2022.10200
|View full text |Cite
|
Sign up to set email alerts
|

Notch1-Jagged1 Signaling Pathway in Oral Squamous Cell Carcinoma: Relation to Tumor Recurrence and Patient Survival

Abstract: BACKGROUND: Dysregulated Jagged1/Notch1 signaling has been implicated in a variety of carcinomas, but little is known about the expression and possible role of Jagged1 and Notch1 in patients with oral squamous cell carcinoma (OSCC). AIM: We set out to examine the clinical significance of Notch1 and Jagged1 expression in OSCC. METHODS: Specimens were obtained from 44 patients who underwent surgical resection of primary OSCC. Immunostaining was done for Notch1 and Jagged1. The utilized markers’ expressions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…19 NOTCH1 protein are heterodynamic proteins. 21 There are three domains of NOTCH1 gene receptor; extracellular, transmemberane and intracytoplasmic. The extracellular domain is responsible for ligand binding, while the intracytoplasmic domain facilitates signal transduction.…”
Section: Notch1 Receptorsmentioning
confidence: 99%
“…19 NOTCH1 protein are heterodynamic proteins. 21 There are three domains of NOTCH1 gene receptor; extracellular, transmemberane and intracytoplasmic. The extracellular domain is responsible for ligand binding, while the intracytoplasmic domain facilitates signal transduction.…”
Section: Notch1 Receptorsmentioning
confidence: 99%
“…Recently, it was reported that a STAT3-activated long non-coding RNA, hepatocyte nuclear factor 1 homeobox A antisense RNA 1, promoted tumorigenesis by activating the Notch pathway in OSCC cells[ 67 ]. Further, high expression of NOTCH1 and JAG1 have been shown to be predictors of poor OS as well as DFS in oral carcinoma patients[ 68 ]. The notch signaling pathway and its role in TSCC is shown in (Figure 3 ).…”
Section: Molecular Signalingmentioning
confidence: 99%